Evaluation of emotional, Behavioral, and clinical characteristics of children aged 1–5 with a history of food-related anaphylaxis - Zeynep Şengül Emeksiz; Aysegul Ertuğrul; Sabide Duygu Uygun; Serap Özmen (Pediatrics and Neonatology)
Background: Our study aimed to investigate emotional, behavioral, and social characteristics assessed with internationally validated psychometric scales and their relationship with demographic, clinical, and laboratory data in children with a history of food-related anaphylaxis. Method: The study included patients aged 1–5 who were followed up in the pediatric allergy outpatient clinic with a diagnosis of food-related anaphylaxis. All participants were evaluated during admission to the clinic using a study questionnaire, which was prepared by the authors, consisting of three parts: a sociodemographic information form, a clinical evaluation form, and the Aberrant Behavior Checklist (ABC) for psychiatric evaluation. Parents answered the questionnaires regarding the patients’ emotional and behavioral health. Results: Thirty patients aged between 12 and 62 months were included in the study. The data were compared with 30 healthy controls with similar age and gender distribution. The total ABC score (p = 0.015), and the stereotypic behavior (p = 0.003) and hyperactivity (p = 0.002) subscale scores were significantly higher in patients with anaphylaxis history compared to the controls. Conclusion: Emotional and behavioral status assessments and the clinical follow-up of food allergies of patients who experienced anaphylaxis in early childhood are useful for the holistic management and early recognition of possible pathologies.